1983
DOI: 10.1055/s-0028-1091421
|View full text |Cite
|
Sign up to set email alerts
|

Decision Matrix and Information Theory Analyses in the Evaluation of Neuroaudiologic Tests

Abstract: Traditionally, diagnostic auditory tests for cochlear versus eighth nerve disorder have been evaluated by the tests' ability to detect patients with eighth nerve disorder (positive result) and to reject patients without eighth nerve disorder (negative result), in other words, the percentage of positive results in patients with eighth nerve site and the percentage of negative results in patients with cochlear site. Recently, several investigators (Galen and Gambino, 1975;Lusted, 1978;McNeil et al., 1975;Thorner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Several investigators have used these operating characteristics to study the peripheral battery for differentiating cochlear versus nerve VIII disorders. [8][9][10] Although there have been studies comparing various CANS tests for subjects with brain injury, 1112 most researchers using CANS tests only have reported test sensitivity. The following discussion is based on 183 subjects of the VHIS who received the three dichotic speech tests.…”
Section: Dichotic Test Efficiencymentioning
confidence: 99%
“…Several investigators have used these operating characteristics to study the peripheral battery for differentiating cochlear versus nerve VIII disorders. [8][9][10] Although there have been studies comparing various CANS tests for subjects with brain injury, 1112 most researchers using CANS tests only have reported test sensitivity. The following discussion is based on 183 subjects of the VHIS who received the three dichotic speech tests.…”
Section: Dichotic Test Efficiencymentioning
confidence: 99%
“…During the past decade, we have witnessed the emergence, development, and refinement of the auditory brainstem response (ABR) to the level of a potent and valuable clinical tool. Several workers have documented the superb operating characteristics of this test [1][2][3] and have shown that, among the myriad of auditory procedures, ABR has consistently demonstrated higher sensitivity and specificity. Consequently, it is presently considered a flagship auditory technique in the diagnostic arenas of audiology, neurotology, and neurology.…”
mentioning
confidence: 99%
“…These variables may contaminate test results, thereby compromising sensitivity and specificity. [4][5][6][7] It is common to discover that data for central auditory tests were gathered from a very small group of subjects or from subjects with generalized lesions or anatomically illdescribed involvement. Subsequent claims of high sensitivity and specificity for these procedures should be viewed cautiously.…”
mentioning
confidence: 99%